Effectiveness of Mung Bean Sprout Extract and Vine Type on the Growth of Pepper (Piper nigrum L.) Plant Cuttings - Tiara, Dewi; Adnan; Mardian Apriansi; Haryuni (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2023)
Abstract : Pepper is a vine and has a single green leaf with a stem height of almost 10 meters. Bengkulu Province is one of the pepper producers in 2021 of 1,850 tons/year with a percentage of 1.31%, of course it cannot meet market demand which is quite high. The decline in pepper production is thought to be caused by several factors, one of which is the lack of good pepper plant seeds available because most farmers plant pepper vines directly on the land without any treatment so that farmers have difficulty cultivating pepper plants. Pepper seeds can be obtained from generative or vegetative propagation. Propagation by cuttings is the recommended method in pepper nurseries. Pepper cuttings have poor roots, so a growth regulator is needed to stimulate the roots. The alternative is by giving Growth Regulatory Substances. One ZPT that can be used to accelerate the growth of pepper plant cuttings is mung bean sprout extract. This research was conducted from February to April 2023, in Taba Tebelet Village, Kepahiang District, Kepahiang Regency, Bengkulu province. This study used a completely randomized design (CRD) with 24 treatment combinations, each of which was repeated three times. Total plants used in the study (K X S X U) = (6X4X3) = 72 plant cuttings. Variable observations were growth percentage, shoot length, root length, number of leaves, stem diameter, and number of shoots. Observational data were analyzed statistically using analysis of variance (ANOVA). The results of this study indicated that the combination treatment of mung bean sprout extract concentration and type of tendrils had a significant effect on the growth of pepper plant cuttings. However, in the single treatment the concentration of sprout extract and the single treatment of the type of tendrils had no significant effect on the growth of pepper plant cuttings.